Czytając między wierszami. Rodzinna Europa Czesława Miłosza i jej angielski/amerykański przekład - Biegajło, Bartłomiej (Wydawnictwo Naukowe UAM, 2011)
The aim of this article is to discuss the problem of translating Polish prose, based on an analysis of a selection of samples taken from Czesław Miłosz’s Native Realm. A Search for Self-Definition translated by Catherine S. Leach. The book documents specific relations between the Western and the Eastern Europe determined by historical provenance of the realms in question. The dichotomy of the collective European history has a profound influence on the reception of Polish literature among the Western audience. Native Realm showcases the issue perfectly – it is interesting in terms of its careful account of the historical and social development of the Continent. The perception of reality is conditioned by an inherent dissimilarity of experiences between the West and the East. The intention of Miłosz was to provide an analysis of them and produce an insightful book addressed specifically to the Western readership. My discussion is an attempt to prove that the endeavour is doomed to failure due to the intrinsic differences between the cultures involved, as cultural inheritance determines the interpretation of historical facts and prompts dissimilar connotations. In the case of Native Realm, on the one hand, we encounter Miłosz’s vision/imagination that is irreversibly rooted in the Slavic way of looking at things and, on the other, the distinctively dissimilar Western vantage point. Translating these differences appears to be a major challenge for any translator.
Reading between the lines. Czesław Miłosz’s Native Realm. A Search for Self-Definition and its English/American translation